Assessment Of Chemical Fertilizers On Water Quality Of Hathaikheda Reservoir Of Bhopal (M.P.) - GANESH RAM NAMDEV,; AVINASH BAJPAI,; SUMAN MALIK, (International Journal of Pharma and Bio Sciences, 2011)
The use of chemical fertilizers in the catchment area of the Hathaikheda Reservoir has increased manyfold. The residual impact of the chemical fertilizer as well as agriculture waste inflow in the lake considerably increased the water pollution problem. The residues of the chemical fertilizer reaching to the Hathaikheda Reservoir with storm water enriched the reservoir water with the loading of nutrients. The extra loading of the nutrient caused eutrophication that supports luxuriant growth of macrophytes. Several physicochemical parameters such as pH, conductivity, Dissolved Oxygen (DO), Biological Oxygen demand (BOD), Chemical Oxygen demand (COD), Nitrates, Phosphates and Potassium were analyzed. Comparison of water quality of Hathaikheda Reservoir Bhopal was carried out in the slight of assessment of impact of use of fertilizers in different areas. During the study high concentration of nutrients were observed in the areas where chemical fertilizer is being used in comparison to other sampling station.